Pengaruh Angka Harapan Hidup dan Pengeluaran Per Kapita Terhadap Tingkat Kemiskinan di Kota Padangsidimpuan - Ahmad Mahadi Rambe; Nursalamah Nursalamah; Asmul Fauzi; Fakhrurrozi Fakhrurrozi (Journal of Islamic Economics and Finance, 2024)
Poverty is one of the fundamental issues that is the focus of government attention in any country. In general, poverty is defined as a condition of inability of income to meet basic needs so that it is less able to guarantee survival. This study is a quantitative descriptive study and aims to determine the Effect of Life Expectancy and Per Capita Expenditure on Poverty Levels in Padangsidimpuan City. The data collection procedure in this study is secondary data in the form of Life Expectancy data, Per Capita Expenditure and Poverty Level data for Padangsidimpuan City in 2017-2022. The tests carried out are Validity Test, Reliability Test, Normality Test and Statistical Test. The data analysis technique in this study is a simple linear regression test, namely the R2 test, F Test and T Test. Based on the results of the study, it can be concluded that the Effect of Life Expectancy on Poverty in Padangsidimpuan City. shows the results - t count for -0.029 and the value -t table with a significant value of 0.05 and df = (n-k), so that df = (13-3) = 10 so the t table value is 2.65 and it can be concluded that t count < t table, namely -0.029 < 2.65 so that H0 is accepted, then Life Expectancy has an effect on Poverty in Padangsidimpuan City. The Effect of Per Capita Expenditure on Poverty in Padangsidimpuan City. shows the results – t count for 0.304 and the value of -t table with a significant value of 0.05 and df = (n-k), so that df = (13-3) = 10 so the value of t table is 2.578 and it can be concluded that t count < t table is 0.034 < 2.65 so that H0 is accepted, then Per Capita Income does not affect Poverty in Padangsidimpuan City. – t count for -0.630, and the value of -t table with a significant value of 0.05 and df = (n-k), so that df = (13-3) = 10 so the value of t table is 2.65 and it can be concluded that t count < t table is -0.630 < 2.65 so that H0 is accepted, then Economic Growth has an effect on Open Unemployment in Padangsidimpuan City. The Effect of Minimum Wages on Open Unemployment in Padangsidimpuan City Padangsidimpuan. shows the results - t count for 2.578 and the value -ttable with a significant value of 0.05 and df = (n-k), so that df = (13-3) = 10 so the value of ttable is 2.578 and it can be concluded that tcount <ttable is 2.578> 2.65 so that H0 is accepted, then the Minimum Wage has an effect on Economic Growth